-3=x+-4

Simple and best practice solution for -3=x+-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3=x+-4 equation:


Simplifying
-3 = x + -4

Reorder the terms:
-3 = -4 + x

Solving
-3 = -4 + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
-3 + -1x = -4 + x + -1x

Combine like terms: x + -1x = 0
-3 + -1x = -4 + 0
-3 + -1x = -4

Add '3' to each side of the equation.
-3 + 3 + -1x = -4 + 3

Combine like terms: -3 + 3 = 0
0 + -1x = -4 + 3
-1x = -4 + 3

Combine like terms: -4 + 3 = -1
-1x = -1

Divide each side by '-1'.
x = 1

Simplifying
x = 1

See similar equations:

| 36=1y-5y-12 | | 4.8=1.8-0.6 | | 20+10x+25x=5.50 | | 7(b-3)=7b+2 | | (-a^3-5a^2)+(4a^3+7a^2+9)= | | -10+-13x+3x^2=0 | | 7w-6=4(w+6) | | 0.6x+8=11 | | 5b+15=60 | | (5a^3-4a+2)+(-7a^3-5a+2)= | | m-15=25 | | 4x+1=2x+6 | | 10j=100 | | 4(m+5)+6=7(m+3)-8m | | 65=4b+5 | | 4x-6=10x+10 | | 4x-9=3-(x-2) | | 18k+27= | | 2x-7+3x=11+x+2 | | 4(3c-2)=9c-7 | | 5-3(2d+5)=2 | | 6d+5=11 | | .6666667q-2=.3333333q+7 | | y+25=40 | | (3x+10)+(7x-30)=180 | | 9-8.2= | | 9(2k+3)= | | 5x+4(3x-16)=140 | | -6x+40=-3x-11 | | 0.5x^2*x^2=0 | | 2x+8=4x-128 | | 6x^2-x+13=0 |

Equations solver categories